An empirical investigation into student's mathematical word‐based problem‐solving process: A computerized approach. - Chadli, Abdelhafid; Tranvouez, Erwan; Dahmani, Youcef; Bendella, Fatima; Belmabrouk, Karima (Journal of Computer Assisted Learning, 2018)
This study proposes a computer‐assisted system with a design based on Polya's problem‐solving model. The system is designed to help average and low‐achieving second graders in mathematics with word‐based addition and subtraction questions. The emphasis of using the specific model was on dividing the problem‐solving procedure into stages and the concentration on the stages that are problematic for students. Specifically, we compared mathematical word problem‐solving performance and computational skills of students who utilized the computer‐assisted system with students who employed general strategy instruction. Participants consisted of 52 second‐grade students randomly assigned to treatment conditions. Students were pretested and posttested with mathematical problem‐solving and computation tests, and repeated measures of their progress with respect to word problem solving were registered. The results showed there was a significant difference between the experimental and control groups in terms of the word problem‐solving progress measure, favouring the experimental group. This confirms that providing students with a computer‐assisted system offered the opportunity to explore all stages of the problem‐solving procedure as one possible way to enhance their problem‐solving skills. Lay Description: What is currently known about the subject matter Problem‐based learning is recognized as an instruction method that positively influence learning outcomes along with higher order thinking skills.The use of computers to implement findings from qualitative research related to problem‐solving teaching strategies can develop reasoning skills in mathematics and problem solving of elementary students with learning difficulties in mathematics.Polya's model helps students to solve mathematical word‐based problems. What the paper adds to this subject This paper suggests that efforts to improve word problem solving should focus on episodes students neglect when solving problems.This study proposes a computer‐assisted system with a design based on Polya's problem‐solving model.This empirical study investigates whether providing students with computer‐based assistance at each stage of the problem‐solving process helps students to overcome their difficulties.This study explores whether students fail to solve the problem because they do not understand the specific relations among the three problem quantities, or in choosing a correct solution strategy, or in carrying out the solution strategy correctly. The implications of study findings for practitioners Combining Polya's model with computer assistance at each solving procedure stage enhances student's capabilities to solve mathematical word‐based problems.Students encountered problems when reviewing their solutions; this signifying that students did not recognize the variants of the problem.